Bacterial pore sealing as a tool for chemical risk reduction - García, José Luis; Serrano-Martinez, Damián; Coulon, Frederic; Posada-Baquero, Rosa; Fernandez Lopez, Carmen; Ortega-Calvo, José Julio (American Chemical Society (ACS), 2026)
Hydrophobic organic compounds (HOCs) such as naphthalene are persistent environmental contaminants whose mobility and bioavailability challenge conventional remediation. Sorptive amendments such as biochar can reduce HOC mobility but may introduce pollutants and lose sorption capacity over time. In this work, we investigated whether the bacterium Bacillus subtilis, biochar, and mixtures of bacteria and biochar could seal pores and impede naphthalene diffusion. We employed two experimental approaches: (i) centrifugation-compacted layers over solid naphthalene (simulating source-zone conditions) and (ii) bioreactors with 3 and 12 μm membranes representing distal transport. B. subtilis exhibited a higher sorption affinity than biochar alone (Freundlich capacity or log K F of 4.33 vs 3.47) and reduced naphthalene mobilization 3-fold, releasing only 2% of the applied mass. The mixture of biochar and bacteria achieved the greatest reductions in naphthalene flux (70% and 50% for 3 and 12 μm membranes, respectively), with effective diffusivities 2 orders of magnitude lower than molecular diffusion through water. Electron microscopy confirmed pore occlusion by bacterial extracellular polymeric substances and biochar aggregation. These findings demonstrate microbial pore sealing as a promising strategy to limit HOC diffusion in porous media, with potential applications for source-zone and plume containment.
Keywords: naphthalene diffusion; Bacillus subtilis; biochar; bioremediation; microbial poresealing; contaminant immobilization; 4102 Ecological Applications; 41 Environmental Sciences; 4004 Chemical engineering; 4105 Pollution and contamination